He Response Of Some Triticum Aestivum L. Genotypes To Drought Stress Based On Morpho-Physiological Traits And Some Yield Components Under Protected House Conditions. - عبد العزيز, محمد; خلاصي, حسام الدين; برهوم, لبنى اكرم (Latakia University Journal -Biological Sciences Series, 2020)
The research was carried out during the agricultural season (2018-2019) within the village of the Dreikish area in Tartous Governorate, to study the effect of three drought stress treatments ( control, 30%, 50% and 70% of field capacity) in five strains of Soft wheat: ACSAD 1256, Doma 58847, Doma 58585, Doma 64453, ACSADA 1149, and two certified varieties Douma4, Doma2 and the effect of interaction among them on some physiological traits (leaf surface and chlorophyll leaf content) in stage 45Z(10 days before flowering) and the proline leaf content in stage 70Z( 10 days before maturity) and some morphological traits(plant height and spike length)and some productivity traits(number of grains per spike, weight 1000s in 70Z. The experiment were cultivated protected (under controlled conditions). The experiment was designed using the design of complete randomized sectors (RCBD), and with three replications, The ACSAD 1256 strain in stage 45Z showed a significant increase in the mean value ​​of foliar surfaces compared to the remaining strains and studied varietie, The treatment also showed at 70% a significant increase in the mean value ​​of the leaf area compared to the other varieties and strains studied, while the treatment exceeded 30% over the rest of the treatments in the mean Evaluate the leaf content of proline. and the interaction between the ACSAD 1256 strain and stress factors was present. Significant differences in mean values ​​of foliar surface, and leaf content of proline. ACSAD 1256 strain in stage 45Z outperformed all other strains and varieties studied in average plant height and spike length values. This oxidation 1256 in stage 70Z also showed a significant increase in the mean values ​​of spike pills and weight 1000s, The interaction between the varieties, strains, and studied parameters showed no significant differences when wheat varieties and strains interacted with the studied parameters in the average values ​​of plant height and number of grains per spike The interaction between the varieties, strains, and studied parameters showed significant differences in the mean values ​​of spike length and the weight of a thousand beads at the level of significance ( p <0.05).